KAJIAN HADIS ERA ANDROID (Telaah Aplikasi ‘Masuk Surga’ Karya Ahmad Lutfi Fathullah) - Fahrudin Fahrudin (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
Hadith studies have experienced very rapid development. This is because many developing various applications or software that can facilitate the study of Hadith. The application and software are then not only a tool in the research activities of Hadith, but also for the benefit of studying the Hadith by the general public. Thus, the application or software must be developed so that it can be sought after and used by the general public. One such application is